2005
DOI: 10.1590/s0103-50532005000100004
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the interaction between humic substances and conducting polymers for sensor application

Abstract: Neste trabalho, foi investigada a interação entre substâncias húmicas e um polímero condutor (poli-(o-etoxianilina) -POEA), ambos em solução e filmes automontados. Os resultados mostram que as substâncias húmicas dopam a POEA por protonação, isto é evidenciado por espectroscopia UV-Vis e Raman. Os estudos de microscopia de força atômica (AFM) em filmes automontados mostram haver um aumento na rugosidade do filme polimérico quando este é exposto a substâncias húmicas (ácidos húmico e fúlvico), o que evidencia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
2
12
0
1
Order By: Relevance
“…The PB is the fully oxidized form of polypyrrole and is insulating in nature [46]. The UV spectrums of PPy films synthesized on copper in sodium acetate and sodium benzoate solutions are shown in Fig.…”
Section: Spectroscopic Characterization Of the Produced Ppy Filmsmentioning
confidence: 99%
“…The PB is the fully oxidized form of polypyrrole and is insulating in nature [46]. The UV spectrums of PPy films synthesized on copper in sodium acetate and sodium benzoate solutions are shown in Fig.…”
Section: Spectroscopic Characterization Of the Produced Ppy Filmsmentioning
confidence: 99%
“…Venancio et al 15 demonstrated that the properties of HS can be used in the fabrication of sensor arrays for use in the classification of humic substances present in aqueous systems, as well as the possibility of using HS for the production of self-assembled films. A novel and simple method electrode with rapid preparation was developed with humic acid and polypyrrole.…”
Section: Maccarthymentioning
confidence: 99%
“…The size of the globules is comparable to the aggregates of polymer molecules in solution. Significantly, the adsorption mechanisms and film properties for polyanilines are altered by a mere change in pH [14], which has been exploited in sensors and other applications [15].…”
Section: Contact Modementioning
confidence: 99%